Application of Frequency-conversion Technology in Fans of Boiler - TAO Zhi-yong (Gong-kuang zidonghua, 2011)
In view of problems of big impact to power grid, serious energy waste caused by operation mode of industrial frequency of blower and fan of boiler of Yuandian No.2 Coal Mine, the paper proposed an improved method with frequency-conversion technology, analyzed energy saving principle of frequency-conversion, control principle of frequency-conversion and effect of energy saving. By use of frequency-conversion technology for fan device to regulate speed and air volume of motors, output and input of air volume of boiler can be accurately adjusted, so as to improve thermal efficiency and combustion efficiency of boiler and reduce energy consumption remarkably with 30%～40% average value of saving energy.